PERAN DINAS KOPERASI DAN USAHA MIKRO KOTA SEMARANG SEBAGAI PENGGERAK UMKM DI ERA PANDEMI COVID-19 - Mutiara Nafisha Putri; Aufarul Marom; Herbasuki Nurcahyanto (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The Covid-19 pandemic began to enter Indonesia on March 2020 and had an impact on the global economy, especially the MSME sector. Micro entrepreneurs experience decreased turnover, lack of capital, and lack of online sales knowledge. The Office of Cooperatives and Micro Enterprises in the City of Semarang as the agency responsible for the welfare of MSMEs in the City of Semarang carries out its role in overcoming MSME problems in the Covid-19 pandemic era. The purpose of this research is to analyze the role of the Cooperatives and Micro Enterprises Office of Semarang City through MSME driving programs in economic recovery during the Covid-19 pandemic era and to find out the driving and inhibiting factors of MSME driving programs in economic recovery in the Covid pandemic era -19 based on Ryass Rasyid's role model of the primary government function. The research method used is descriptive qualitative using primary data sources obtained through in-depth interviews and field observations as well as secondary data. The results of the study show that the role of the Office of Cooperatives and Micro Enterprises in the City of Semarang through MSME driving programs is going well through the four governmental roles, namely the service function, the regulatory function, the development function, and the empowerment function. In the implementation of MSME driving programs there are driving factors, namely community participation and environmental conditions, as well as inhibiting factors, namely program characteristics. Suggestions from researchers are employees of the Semarang City Cooperatives and Micro Enterprises Office to optimize assistance to micro entrepreneurs during training and program sustainability. Coordination and collaboration with the Kopimi Outlet Community can help restore the economy of the Covid-19 pandemic.